Effect of antagomir-22-3p treatment on skeletal muscle growth in intrauterine growth-restricted lambs - Duckett, S. K.; Greene, M. A.; Udoka, A. N. S.; Powell, R. R.; Bruce, T. F.; Klotz, J. L. (Frontiers in Molecular Biosciences, 2025)
IntroductionMicroRNAs (miRNAs) play a crucial role in regulating gene expression and muscle development. Previous research identified miR-22-3p as being differentially regulated during muscle hypertrophy, and in vitro experiments found that antagomir-22-3p enhanced satellite cell proliferation. The objective of this study was to evaluate the in vivo vascular injection of antagomir-22-3p into the lateral saphenous vein and its effect on miRNA and histone deacetylase (HDAC) family mRNA expression in intrauterine growth restriction (IUGR) lambs.MethodsPregnant ewes (n = 18) carrying twins were fed either 100% of NRC (CON) or were nutrient-restricted to 60% NRC (NR) from gestational d 86 until parturition. On d 12 of age, NR lambs (n = 8) were randomly selected and given a systemic injection of antagomir-22-3p (440 µg/lamb) into the lateral saphenous vein of the right leg (NR-ANT22) for three consecutive days. CON lambs (n = 8) were also randomly selected and received a sham injection of phosphate-buffered saline (PBS) into the lateral saphenous vein of the right leg (CON-SHAM). Blood samples were collected from each lamb weekly to monitor circulating miR-22-3p expression. Muscle samples were collected 24 days post-injection to assess miR-22-3p levels and mRNA expression of potential miRNA targets.Results and discussionCell-free circulating miR-22-3p expression was more downregulated (P < 0.05) in NR-ANT22 lambs compared to that in CON-SHAM on d 14 after injection. On d 21 after injection, miR-22-3p expression in plasma tended to be more downregulated (P = 0.08) in NR-ANT22 compared to CON-SHAM. Lamb body weight and muscle weights at harvest were similar between the NR-ANT and CON- SHAM treatment groups. In the semitendinosus (ST) muscle, miR-22-3p expression was more downregulated (P < 0.05) in NR-ANT22_R ST (treated) lambs compared to that in NR-ANT22_L ST (non-treated) and CON-SHAM ST. In the heart and semimembranosus (SM) muscles, the expression of miR-22-3p was more downregulated (P < 0.05) in NR-ANT22 compared to that in CON-SHAM. In the gastrocnemius muscle, miR-22-3p expression remained unchanged (P > 0.05). The number of types I, IIa, and IIax muscle fibers were greater (P < 0.05) in NR-ANT22 lambs than those in CON-SHAM, whereas the number of type IIx fibers was greater (P < 0.05) in CON-SHAM lambs. NR-ANT22 treatment appears to promote a shift toward more oxidative muscle fiber metabolism. The systemic injection of antagomir-22-3p downregulated miR-22-3p expression in circulation and muscle tissues, which, in turn, altered the expression of HDAC/SIRT genes involved in muscle fiber type conversion and hypertrophy.